Atrial Fibrillation Is an Independent Risk Factor for Hospital-Acquired Pneumonia - Zhu, Jinxiu (PLoS One, 2015)
BACKGROUND: Patients who were hospitalized for community-based pneumonia frequently had pre-existing atrial fibrillation (AF) and had subsequent cardiovascular complications. Whether patients who had AF would be susceptible to the development of hospital-acquired pneumonia (HAP) is a serious concern but this has not been investigated. In our clinics, we have made empirical observation of such susceptibility. OBJECTIVES: To investigate the association between newly developed HAP and pre-existing AF, and to identify whether AF is an independent risk factor for HAP. METHODS: Hospital data from 8657 sequentially admitted inpatients [1059 patients with AF and 7598 without AF (NAF)] were collected from the Department of Cardiology, First Affiliated Hospital of Shantou University Medical College, Shantou, China, from January 1, 2009 to December 31, 2011. Exclusion criteria were: having previous or current pneumonia, pacemakers, sick sinus syndrome and repeated hospitalization. The incidence of HAP (within 48 hours after hospitalization) was identified among all the patients. RESULTS: Among the AF patients, 274 had HAP (adjusted rate 25.64%) which was significantly higher than the 276 NAF patients who had HAP (adjusted rate 3.66%; P<0.001). The increased risk was also associated with high blood pressure, heart failure and age, but not with gender, smoking, coronary heart disease, diabetes, congenital heart disease. In addition, our multiple regression analysis indicates that AF is an independent risk factor for HAP. CONCLUSION: We have identified, for the first time, that AF is an important risk factor for HAP. Although additional clinical confirmation is needed, our data provide valuable evidence for use in prevention of HAP which is the most common cause of death from nosocomial infection.